PERANCANGAN SISTEM HIBRID PEMBANGKIT LISTRIK TENAGA SURYA DENGAN JALA-JALA LISTRIK PLN UNTUK RUMAH PERKOTAAN - Liem Ek Bien, Liem Ek Bien; Kasim, Ishak; Wibowo, Wahyu (Jurnal Teknik Elektro, 2008)
Solar cell is one of renewable energy. Solar cell can convert directly sunlight dissociationenergy of diatomic to become electric energy. Electric energy yielded by solar cell hardlyinfluenced by the sun intensity of light received, so that solar cell can only yield electricenergy if there are sunlight. Supply of electric energy should be able to be applied everytime. Hybrid of solar energy alternator (PLTS) with electrical grid of PLN will yieldcontinuous supply of electric energy. At this hybrid system, electrical supply from PLTS isdesigned to be around 30% from overall load of electrical equipment in household, the restload around 70% is fulfilled by PLN.Hybrid process of PLTS with the electrical grid iscontrolled by a switch controller which its working principal based on one way direction;when PLTS works (on), hence electric supply from PLN is disconnected and so vice versa.Keywords: solar cell, hybrid system, switch controller